Effectiveness of screening for tuberculosis in HIV: a pragmatic clinical trial - Santos, Marcela Lopes; Batista, Joanna d’Arc Lyra; Braga, Cynthia; Silva, Adriana Paula da; Maruza, Magda; Souza, Wayner Vieira; Carvalho, Maria Rosimery de; Siqueira-Filha, Noemia Teixeira de; Albuquerque, Maria de Fátima Pessoa Militão de (Revista de Saúde Pública, 2021)
OBJECTIVE: To verify the effectiveness of screening for tuberculosis (TB) on all-cause mortality and tuberculosis cases in newly diagnosed HIV-infected patients through a clinical algorithm based on recommendations of the World Health Organization. METHODS: From March 2014 to April 2016, a pragmatic randomized clinical trial was conducted with newly diagnosed and TB-free HIV-infected adults undergoing antiretroviral therapy for up to one month at a major tertiary hospital for HIV in the state of Pernambuco, Brazil. Participants were randomized into intervention and control groups using an automatically-generated random list, and followed-up for at least 6 months. The intervention group was screened for TB at hospital admission and at every follow-up visit through a series of questions addressing TB-related symptoms (cough, fever, night sweating, and weight loss). Patients presenting with any of these symptoms were referred to a pulmonologist and underwent sputum smear microscopy, sputum culture, and rapid molecular testing (GeneXpert). When at least one test result came back positive, TB treatment was initiated. In turn, if patients tested negative but presented with severe clinal symptoms, TB preventive treatment was initiated. Screening for TB was not performed systematically in the control group. The primary outcome assessed in this study was death from all causes, and secondary outcomes included sensitivity and specificity of this screening test, as well as its detection time. RESULTS: This study evaluated 581 patients, 377 in the intervention group (64.9%) and 204 in the control group (35.1%). In total, 36 patients died during the follow-up period. Of these, 26 (6.9%) were from the intervention group, reaching a cumulative mortality coefficient of 69 per 1,000 inhabitants, and 10 (4.9%) from the control group (p = 0.341), with a cumulative mortality coefficient of 49 per 1,000 inhabitants (p = 0.341).